Respuesta :

Answer:x             f(x) = 2.5x − 10.5              g(x) = 64(0.5x)

2            f(2) = 2.5(2) - 10.5             g(2) = 64(0.5*2)

             f(2) = 5 - 10.5                    g(2) = 64(1)

             f(2) = -5.5                          g(2) = 64

3            f(3) = 2.5(3) - 10.5             g(3) = 64(0.5*3)

             f(3) = 7.5 - 10.5                 g(3) = 64(1.5)

             f(3) = -3                             g(3) = 96

4            f(4) = 2.5(4) - 10.5             g(4) = 64(0.5*4)

             f(4) = 10 - 10.5                  g(4) = 64(2)

             f(4) = -0.5                          g(4) = 128

5            f(5) = 2.5(5) - 10.5             g(5) = 64(0.5*5)

             f(5) = 12.5 - 10.5               g(5) = 64(2.5)

             f(5) = 2                              g(5) = 160

6            f(6) = 2.5(6) - 10.5             g(6) = 64(0.5*6) 

             f(6) = 15 - 10.5                  g(6) = 64(3)

             f(6) = 4.5                           g(6) = 192